East Asia Update, October 2003 : From Cyclical Recovery to Long Run Growth - World Bank (World Bank, Washington, DC, 2020)
The region had already begun a cyclical recovery in 2002, but this was partially side-tracked by SARS - Severe Acute Respiratory Syndrome - and other shocks in early 2003. East Asian growth fell to only 3 percent in the second quarter of 2003. On balance, though, the impact of SARS was less than first feared, and growth projections for 2003 remain unchanged, compared with six months ago. Far from too little growth, China is in the midst of a powerful boom that has policy makers looking for ways to cool the pace of expansion in some sectors. On the other hand, export growth in most East Asian countries, slowed in the summer, and in some has yet to revive. These conflicting signals obscure somehow the near term outlook, but, on balance, prospects for East Asia are getting brighter. If the momentum of reform can be maintained, the region should be well placed to convert cyclical recovery into more sustained, long run growth. There are four sets of reasons for optimism: the global economy is improving, continued strong growth in China is propelling a vast expansion in its imports from the rest of East Asia, post-financial crisis " fire-fighting " seems to be behind, with domestic conditions in the region improving, and, the region is becoming more comfortable with representative forms of governance. However, two dangers deserve special attention: international trade is the life blood of East Asia, but the setback at the Cancun trade talks, might allow protectionist interests to go on the offensive, causing long term damage to the world trading system; and, within East Asia progress on institutional, and governance reforms has been slow, evidently hurting its competitive position in the world. Several priority policies are suggested, namely prudent macroeconomics, continued emphasis on strengthening financial sector supervision and regulation, corporate governance, and the supporting legal and judicial framework for the financial, and corporate sectors, as well as fostering the development of more diversified capital markets, to better handle different kinds of risks. The report also looks at the prospects for economic growth in the region, its poverty incidence, and at a more supportive international environment, pointing at improved confidence, demand, and activity, underpinned by supportive monetary, and fiscal policies adopted by many countries. Domestic trends and policy challenges convey gradual improvements in the financial sector, more active capital market development, improved corporate governance, and political transitions in several countries in the region.